“Developing Critical Thinking and Creativity in 5th–7th Grade Students through Visual Arts Education - Vosiyeva Aziza To‘xtaqulovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article explores strategies for developing critical thinking and creativity in 5th–7th grade students through visual arts education. It emphasizes the integration of collaborative projects, project-based learning, and innovative pedagogical approaches, including digital tools and experiential activities. The study demonstrates that combining traditional art instruction with modern interactive methods enhances students’ analytical skills, artistic competencies, and imaginative capabilities, fostering holistic cognitive and creative development